Future skill supply in Europe : medium-term forecast up to 2020 - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
Qualifications are rising in Europe, but inequalities persist: The level of qualifications and skills is rising across Europe, particularly among younger people – and even more so among women. But inequalities in the level of education persist among Member States. These are some of the conclusions of the first pan-European forecast of its kind, Future skill supply in Europe: medium-term forecast up to 2020, published by Cedefop. The forecast shows a declining number of people with low qualifications in almost all EU countries and a steady rise in medium (mostly vocational) and high qualifications, both among the labour force and among the general population. (Hrsg.)
Keywords: I 2.2 Europa; G 1.2.3.2 Anforderungen & Bedarfe; S 3.5.5.1 CEDEFOP; Qualifikationsbedarf; Europa; Prognose; 2020